IMPLEMENTASI PANCASILA SEBAGAI STRATEGI PENINGKATAN TOLERANSI DI ERA MODERN INDONESIA - Mario Jonathan Kusuma; Ibthisam Luthfi Rahman; Muhammad Wildanu Rabbani; Muhammad Zulfi Suryafalah; Nazila Rachma Ramadhani (Cahaya Ilmu Bangsa, 2024)
This study examines the implementation of Pancasila values as a strategy to enhance interfaith tolerance in Indonesia within the modern era, characterized by globalization and digital technology. Using a qualitative descriptive approach, data were collected through literature review and social observations. The findings reveal that despite being the state ideology, the application of Pancasila continues to face challenges, including religious radicalism, misinformation on social media, and weak public literacy regarding Pancasila values. The study highlights the crucial role of education in internalizing Pancasila values from an early age, particularly through curricula that emphasize tolerance and unity. Additionally, active participation by communities, interfaith organizations, and the use of social media as platforms for disseminating messages of peace is essential for fostering harmonious relationships. However, major obstacles such as the politicization of religion and inconsistent enforcement of laws against intolerance were also identified. As a solution, the study also recommends strengthening character education based on Pancasila, public campaigns on tolerance, and collaboration among governments, communities, and religious leaders. With a comprehensive strategy, implementing Pancasila values can serve as a robust foundation for building a tolerant and harmonious nation.